The influence of information structure on lexical activation in British English (Linguistics in Amsterdam, 2020)
Previous psycholinguistic studies demonstrated that focus leads to numerous processing advantages (Benatar & Clifton 2014, Birch & Rayner 2010). In the present study, we aimed to investigate the lexico-semantic activation of focused material. Our experiment employed an adaptation of the word change-detection paradigm (Ward & Sturt 2007), in which the properties of focus and change (i.e., semantic synonyms) were manipulated. It is a central claim of Information structure theory that focus denotes the existence of alternatives (Rooth 1985). We observed a tendency of the changed words introduced in focus to elicit faster reaction times. We regard our results as experimental evidence of this claim and we propose that the present results support the idea that focus activates alternatives. When a word is introduced in focus, the focus feature activates alternative items, which elicit faster reaction times for the changed items. Similar results were obtained in two recent lexical decision task studies (Braun & Tagliapietra 2010; Husband & Ferreira 2015).